OP0069 The relationship between estimated bone strength by finite element analysis at the peripheral skeleton to areal bmd and tbs at lumbar spine in adults. (12th June 2018) - Alvarenga, J.C.; Boyd, S.; Pereira, R.
Abstract : Background: Bone strength, estimated by finite element (FE) analysis based on high resolution peripheral quantitative computed tomography (HR-pQCT) images is an important contributor to understanding risk of fracture. However, it is a peripheral device and cannot be evaluated in vivo at lumbar spine L1-L4. Objectives: The aim of this study was to investigate if the axial bone quality can be predicted by strength measurements of peripheral bone. Methods: Peripheral bone microarchitecture, areal bone mineral density (aBMD) and trabecular bone score (TBS) were measured in adults individuals (n=262, 60 years and older; 63% women). Stiffness and failure load were estimated by FE analysis at HR-pQCT images at radius and tibia. Areal BMD and TBS were measured by dual energy X-ray absorptiometry (DXA) at L1-L4. Correlations between peripheral and axial data were estimated for each gender adjusted by age, weight, and height. Results: Areal BMD L1-L4 resulted in weak to moderate significant correlations with stiffness and failure load at radius (women: R²=0.178, p<0.05 and R²=0.187, p<0.001, respectively; men: R²=0.454 and R²=0.451, p<0.001, respectively) and at tibia (women: R²=0.211 and R²=0.216, p<0.001, respectively; men: R²=0.488 and R²=0.502, p<0.001, respectively). TBS showed a very weak or no correlation with stiffness and failure load at radius (women: R²=0.148 and R²=0.150, p<0.05, respectively; men: R²=0.108 and R²=0.106, p<0.05, respectively) and at tibia (women: R²=0.146 and R²=0.150, p<0.05, respectively; men: R²=0.072 and R²=0.078, respectively). Conclusions: These data suggest that aBMD L1-L4 was better explained by peripheral bone strength characteristics than the TBS, mainly in men and tibia is generally the site with a better relationship. Disclosure of Interest: None declared